Intradural enterogenous cyst. - Mohanty, S (1979)
A 23 year old woman with an intradural extramedullary enterogenous cyst in the cervical region, unassociated with vertebral cleft, presented with two episodes of neurological disturbance at an interval of five years. Subtotal excision of the anteriorly placed cyst at C6 vertebral level was followed by rapid and complete recovery.